SOCIAL PROTEST MOVEMENTS IN THE ISLAMIC REPUBLIC OF IRAN - S. B. Druzhilovsky (Vestnik MGIMO-Universiteta, 2015)
The article deals with causes and distinctive features of social protest movements in Iran through the prism of the effect that historic and contemporary developments have on them. The author analyses the most important factors that influence social activity during periods of exacerbating internal tensions in Iran. Great importance is attached to the Shia clergy ́s role in leading protest movements in the country before the Islamic revolution. Besides, the author evaluates the capacity of the ruling clergy to halt protests and ensure the majority ́s loyalty to the governing regime. Considerable attention is paid to the characteristics of the so-called «green movement» in which during 2011–2012. Again loudly declared himself to speak in support of popular uprisings in several Arab countries during the «Arab Spring». Under the influence of these events in Iran have again begun a protest against President Mahmoud Ahmadinejad. In this regard, the Iranian authorities placed under house arrest of several opposition leaders, including Mousavi. Since then, the situation in Iran in general has stabilized. Moreover, the leaders of the «green» M. Mousavi and M. Kyarubi made a number of harsh anti-Western statements, in which he accused the West of choosing «wrong way» to resolve the Iranian nuclear issue by introducing anti-Iranian sanctions. They are, from the point of view of the opposition leaders, especially not hit the economic interests of the Iranian government and the Iranian citizen. The election in November 2013 the new president of Iran representative of the liberal camp Hassan Rouhani also had a positive impact on the containment of the Iranian opposition street protests.